Bioenergetic and immunological characterization of cryopreserved peripheral blood mononuclear cells (PBMCs) isolated from blood and buffy coat - Dieter, Fabian; Grube, Jendrik; Quentin, Alice; Eckert, Gunter P. (Frontiers in Molecular Biosciences, 2026)
BackgroundMitochondrial dysfunction (MD) and inflammaging are hallmarks of non-communicable diseases and play a pivotal role in the ageing process. Determination of mitochondrial function (MF) in Peripheral Blood Mononuclear Cells (PBMCs) represents a minimally invasive method for assessing the pathophysiological state. However, the necessity to measure the cells in a fresh state is a challenge especially in multicenter investigational studies. Therefore, we investigated the mitochondrial and immunological properties of cryopreserved PBMC isolated from whole blood and buffy coats over a storage period of 6 months to establish a procedure to assess MD in frozen samples.MethodsPBMCs were isolated from whole blood and buffy coats using gradient density centrifugation and cryopreserved with fetal bovine serum and dimethyl sulfoxide as antifreeze agents in liquid nitrogen. To identify potential differences between cryopreserved and freshly isolated cells, we investigated cell count and viability, mitochondrial respiration, adenosine triphosphate production, and citrate synthase activity in PBMCs during 6 months of storing. Cell composition was determined using flow cytometry. The immune status was assessed by determining the cytokines IL-6, IL-10, and TNF-α after phytohemagglutinin stimulation using time-resolved fluorescence (HTRF).ResultsAfter cryopreservation and storage of PBMCs isolated from whole blood or buffy coats, their bioenergetic function is preserved for at least 6 months: No statistically significant differences in the parameters CS, ATP, and the complexes of the respiratory chain were observed at any measurement time point. However, fluorescence-activated cell sorting analysis reveals that the number of apoptotic cells increased after 1 month of cryopreservation. After 3 months of cryopreservation, phytohemagglutinin-activated cytokines IL-6, IL-10 and TNF-α were significantly increased, indicating a more sensitized immune response of frozen cells.ConclusionCryopreservation of PBMCs has no effect on the measurement of bioenergetic parameters, although increased apoptotic cells are measured. Cryopreserved PBMCs show an increased immunological response, which must be taken into account when interpreting the results.